Systematic Literature Review Analisa Faktor-faktor yang Mempengaruhi Minat Mayarakat dalam Menggunakan Layanan di Koperasi Syariah - Hanifah Alhusna; Sebastian Herman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to analyze factors that can influence people's interest in using services in sharia cooperatives, where sharia cooperatives have an important role in the economy after banking. This research uses qualitative methods, using the Publish or Perish application to analyze various journals that already exist on Google Scholar. which includes behavioral research on why people choose sharia cooperatives to use the services offered by sharia cooperatives. After that, what variables are found that influence members to want to use services at sharia cooperatives and then analyzed and identified. Using the method of collecting research results based on the reasons why people are interested in choosing to use services in sharia cooperatives that are not yet available, the results of this research can be used as evaluation material and become the basis for sharia cooperatives in designing strategies with significant variables that continue to develop or progress. The results of the analysis show that factors such as trust or religiosity, social and knowledge about sharia cooperatives themselves influence people's decisions in using services at sharia cooperatives. These findings provide insight or can be used as evaluation material for cooperative managers to increase community participation in using services in cooperative institutions.